Contributions of Career Muslim Women of Ilorin Emirate to the Society: Alhaja Meimunat Idi-Agbede in Focus - O. R. Azeez; R. O. Jubril; S. A. Badmus (LECTURES: Journal of Islamic and Education Studies, 2024)
Some contemporary Muslim women have subjected themselves to degradation and subordination due to mixture of cultural patterns with civilization where women are majorly focusing on career development at the expense of their marital responsibilities. However, a number of Ilorin Muslim women have succeeded in keeping a meaningful career as well as discharging their marital responsibilities dutifully. Therefore, this paper aimed at studying the contributions of these women, as career Muslim women, to Ilorin emirate with focus on Alhajja Meimunat Idi-Agbede. The methodology adopt includes historical and descriptive methods. Historical method was used to account for the biography of Alhaja Meimunat Idi-Agbede, while descriptive method was used to describe the career Muslim women in Ilorin emirate in general and the contribution of Alhaja Idi-Agbede in particular. The paper reveal that some notable career Muslim women in Ilorin emirate such as Alhaja Segilola Alaya and Professor Ni’mat Abdur-Raheem have made huge contributions to the society in general and that the contributions of Alhajja meimunat Idi-Agbede are focus more centered on Shamsudeen College of Arabic and Islamic Studies, assistance of the orphans, widows and the needy among others. Therefore, the paper conclude that despite the huge number of contemporary Muslim women who have ventured into having career in men populated domain, a number of them still work-hard to sustain their various homes, by maintaining balance between the two duties. It is therefore recommended that the contributions of these notable career Muslim women be documented and exposed to serve as motivation for other women in Ilorin emirate.